Parkways, Greenways, Riverways : The Way More Beautiful - Appalachian Consortium Press (Appalachian State University, 1989)
The Third Biennial Linear Parks Conference was held in Asheville, North Carolina, on September 19-22, 1989. Contributors to the proceedings are Woodward S. Bousquet; Anne Lusk; Jerry L. Rogers; Noel Grove; Boudewijn Bach; Grant Jones; Li Rusheng; Elizabeth K. Meyer; Richard L. Kent; Yasuo Bansho; Sara Amy Leach; William A. Mann; Paul M. Rookwood; Steven L. Cantor; Janit L. Potter; John W. Bright; Charles Birnbaum; Lois A. Brink and Ann Skarvedt; Eric W. Lyons; Stanton Jones; Paul E. Skidmore; Susanne Christian Sweek; Charles A. Fink; John A. Black; Hao Xu and Karl Schurr; Marnie Muller; Arthur Bender; James M. Wright; Lorah P. Hopkins; Elliott Gimble; James E. Fox; William L. Flournoy Jr.; Richard E. Chenowith; Donald Armstrong and Charles Yuill; Kristina Reichenbach; William E. Shepherd; and Robert M. Searns.
English
Keywords: Service industries; Business & Economics; Industries; Park & Recreation Management